Endophyte Chaetomium globosum D38 Promotes Bioactive Constituents Accumulation and Root Production in Salvia miltiorrhiza - Zhai, Xin; Luo, Dong; Li, Xiuqing; Han, Ting; Jia, Min; Kong, Zhouyang; Ji, Jiachen; Rahman, Khalid; Qin, Luping; Zheng, Chengjian (Frontiers in Microbiology, 2018)
Salvia miltiorrhiza is known for tanshinones and salvianolic acids, which have been shown to have a protective effect against ROS, especially for cardiovascular diseases and other various ailments of human organs. Due to the low yield of tanshinones and their analogs in S. miltiorrhiza, multiple stimulation strategies have been developed to improve tanshinones production in plant tissue cultures. Endophytic fungi have been reported to form different relationships with their host plants, including symbiotic, mutualistic, commensalistic, and parasitic interactions. Thus we take the assumption that endophytic fungi may be a potential microbial tool for secondary metabolism promotion in medicinal plants. We recently isolated Chaetomium globosum D38 from the roots of S. miltiorrhiza and our study aimed to examine the effects of this live endophytic fungus D38 and its elicitor on the accumulation of tanshinones in the hairy root cultures of S. miltiorrhiza. Our results revealed that C. globosum D38 mainly colonized in the intercellular gap of xylem parenchyma cells of S. miltiorrhiza hairy roots during the long term co-existence without any toxicity. Moreover, both of the live fungus and its mycelia extract could increase the production of tanshinones, especially for dihydrotanshinone I and cryptotanshinone. The effect of the mycelia extract was much stronger than that of the live fungus on tanshinones synthesis, which significantly increased the transcriptional activity of those key genes in tanshinone biosynthetic pathway. Furthermore, the live C. globosum D38 could also be made into biotic fertilizer used for S. miltiorrhiza seedlings culture, which not only significantly promoted the growth of the host plant, but also notably enhanced the accumulation of tanshinones and salvianolic acids. We thus speculated that, in the soil environment D38 could form bitrophic and mutual beneficial interactions with the host and enhance the plant growth and its secondary metabolism on the whole so as to have facilitative effects on both tanshinones and salvianolic acids accumulation. In conclusion, Chaetomium globosum D38 was a highly beneficial endophytic fungus for the growth and metabolism of S. miltiorrhiza.